Ammonia Predicts Hepatic Involvement and Pulmonary Hypertension in Patients With Hereditary Hemorrhagic Telangiectasia. Issue 1 (January 2020) - Bloom, Patricia P.; Rodriguez-Lopez, Josanna; Witkin, Alison S.; Al-Samkari, Hanny; Kuter, David J.; Mojtahed, Amirkasra; Luther, Jay
Abstract : INTRODUCTION: Hepatic involvement in hereditary hemorrhagic telangiectasia (HHT) is common and can be associated with severe clinical consequences, including portal hypertension, cardiac failure, and encephalopathy. However, there are no reliable clinical predictors of hepatic involvement and its associated complications, limiting appropriate identification of these patients. In this work, we define the utility of serum ammonia and liver biochemical tests (LFTs) in predicting hepatic HHT involvement and its complications. METHODS: We performed a retrospective study examining a well-characterized cohort of patients with HHT. Clinical characteristics, laboratory tests, liver imaging, transthoracic echocardiography assessment of right ventricular systolic pressure (RVSP), and history of other HHT-related outcomes were assessed. Patients were followed for the development of encephalopathy. RESULTS: Of 45 patients with definite HHT, 18 (40%) had elevated ammonia levels. An elevated ammonia associated with the presence of hepatic arteriovenous malformations (AVMs) on imaging ( P < 0.03) and when combined with elevated liver tests increased the sensitivity for hepatic AVMs by 18% (55% for LFTs vs 73% for LFTs plus ammonia). Furthermore, an elevated serum ammonia in patients with HHT associated with an elevated RVSP (>35 mm Hg), providing an 80% sensitivity and 71% specificity for predicting the presence of pulmonary hypertension. In contrast, there was no association with an elevated serum ammonia and encephalopathy over a total of 859 months of follow-up. DISCUSSION: Elevated ammonia in a cohort of patients with HHT was associated with the presence of hepatic AVMs and elevated RVSP, but no other complications of HHT, including encephalopathy.